Using Apportionment To Rein In The Georgia-Pacific Factors - Bensen, Eric E.; White, Danielle M. (Science and Technology Law Review, 2008)
In a dramatic departure from well-established patent damages law, which would confine a reasonable royalty to a portion of the profit contributed by the infringed patent, current Federal Circuit precedent permits a reasonable royalty on an even relatively insignificant component to exceed not only the profit attributable to that component, but, in some cases, the entire profit on the product. That precedent ignores the history of the reasonable royalty award, which originated as merely a substitute for an “established” or market rate royalty for the patent. Just as the real-life negotiations leading to an established royalty would result in the licensor and licensee splitting the profit attributable to the licensed patent, a reasonable royalty should leave the infringer with a portion of the profit attributable to the patented invention as compensation for its labor, risk, and investment. The Federal Circuit’s precedent also ignores long-standing apportionment principles, which, if properly applied, would not permit a patentee to derive a reasonable royalty from the unpatented features of an infringing product. Unbound as they are from their economic and legal foundations, royalty awards have, not surprisingly, become arbitrary and often punitive. This article argues that to rein in reasonable royalty awards, restore them to their historical role, and ensure that they are consistent with long-standing principles of patent damages law, (i) apportionment should be the threshold question in every reasonable royalty analysis, and (ii) only factors relevant to approximating a fair market price for the patent should be used to determine the “reasonable” royalty. By treating apportionment as a threshold question, courts can ensure that the resulting reasonable royalty award is properly confined to a portion of the profit attributable to the patent. By looking only to factors relevant to approximating a fair market price, as opposed to an individually negotiated price, courts can ensure that reasonable royalties stay true to their original purpose and avoid reliance on the more subjective Georgia-Pacific factors that give experts so much opportunity for obfuscation. While reasonable people will still be able to disagree about the merits of any particular award, following the steps we describe will ensure that reasonable royalty awards are not punitive, but rather, well-grounded in economic and legal reality.